Political process in Spain in a pandemic - A. A. Kurakina-Damir (Ибероамериканские тетради, 2022)
Spain became one of the most affected countries both in terms of the number of cases and deaths from COVID-19, and in terms of the damage caused to the economy, which had not fully recovered from the 2008 crisis. The pandemic crisis is now being tackled by a coalition government comprised of the center-left Spanish Socialist Labor Party (PSOE) and the left-wing Unidas Podemos, with external support from small regional forces. It is opposed by the rightwing bloc of parties, which includes recently shifting to the right Partido Popular (PP), the right-wing Vox and the center-right Ciudadanos, rapidly losing political weight. The key question today is whether the government, which is forced to turn to other parties for help, will be able to fulfill its responsibilities until the elections scheduled for the end of 2023. Last November marked two years since the last elections. The purpose of this article thereto is to determine the main features of the modern political process in Spain and take stock of the government’s actions, analyze expectations of society and predict further development of internal politics of Spain during the pandemic and in the post-pandemic reality. The author used a wide range of methods: the analysis and synthesis of information, the statistical method, as well as the system analysis; the author also relies on research by domestic and foreign Hispanists, opinion polls, government and party documents. The author concludes that the political process in Spain today is subject to negative influence of a strong confrontation between the coalition government and the opposition, and the Spanish society is split on a number of issues.